Data and e-commerce: An economic relationship - Libor Klimek; Rastislav Funta (DANUBE: Law, Economics and Social Issues Review, 2021)
In almost all sectors, online services play a much larger role than a few years ago. Data-driven platform models combine an ever greater degree of market power. The associated concentration effect leads to the displacement of medium-sized companies from the market. When looking at the large platforms of this new digital economy their success model is based almost exclusively on generating data and extracting economically useful information from this data. In relation to trading platforms, the use of data serves among other things to increase efficiency. The so-called data sharing offers numerous advantages that can be leveraged in connection with e-commerce platforms. Due to this, we will first take a closer look at e-commerce and the special economic characteristics of the business model of digital platforms (especially Amazon). The next chapter discusses the current legal framework and focus on the antitrust claims of retailers against online platforms. Then, we will deal with the legal-political approaches to the digital platform economy. The study concludes with various options for action which can be derived from the legal and economic explanations outlined in the previous chapters.
Keywords: 330; Antitrust; Platforms; E-Commerce; Data; B2C; B2B